Quality Overprovision in Cable Television Markets - Crawford, Gregory S.; Shcherbakov, Oleksandr; Shum, Matthew (American Economic Review, 2019)
We measure the welfare distortions from endogenous quality choice in imperfectly competitive markets. For US cable television markets between 1997–2006, prices are 33 percent to 74 percent higher and qualities 23 percent to 55 percent higher than socially optimal. Such quality overprovision contradicts classic results in the literature and our analysis shows that it results from the presence of competition from high-end satellite TV providers: without the competitive pressure from satellite companies, cable TV monopolists would instead engage in quality degradation. For welfare, quality overprovision implies cable customers would prefer smaller, lower-quality cable bundles at a lower price, amounting to a twofold increase in consumer surplus for the average consumer. (JEL L13, L15, L82)